2019
DOI: 10.1186/s40425-019-0632-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells orchestrate innate and adaptive anti-tumor immunity induced by oncolytic coxsackievirus A21

Abstract: Background The oncolytic virus, coxsackievirus A21 (CVA21), has shown promise as a single agent in several clinical trials and is now being tested in combination with immune checkpoint blockade. Combination therapies offer the best chance of disease control; however, the design of successful combination strategies requires a deeper understanding of the mechanisms underpinning CVA21 efficacy, in particular, the role of CVA21 anti-tumor immunity. Therefore, this study aimed to examine the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Moreover, following treatment with recombinant cytokines, IFN-α (not TNF-α or IFN-γ) was implicated in the killing of H929 cells but not U266B cells, suggesting that additional, as yet undefined, cytokines are involved in mediating the overall cytotoxic effects of PBMC-CM ( online supplemental figure S5D ). Although we have not defined the role for individual cytokines in all cell lines, given our previous studies in different HM disease models, 6 it is expected that multiple cytokines will contribute to this effect across different MM cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, following treatment with recombinant cytokines, IFN-α (not TNF-α or IFN-γ) was implicated in the killing of H929 cells but not U266B cells, suggesting that additional, as yet undefined, cytokines are involved in mediating the overall cytotoxic effects of PBMC-CM ( online supplemental figure S5D ). Although we have not defined the role for individual cytokines in all cell lines, given our previous studies in different HM disease models, 6 it is expected that multiple cytokines will contribute to this effect across different MM cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Immature DC were loaded with tumor cells (±reovirus treatment) at a 3:1 tumor cell:DC ratio for 48 hours and tumor-loaded DC were cultured with autologous PBMC at a 1:20-1:30 DC:PBMC ratio in CTL medium. 6 Cells were incubated for 7 days at 37 ºC and re-stimulated with tumor-loaded iDC (±reovirus treatment) for a further 6 days before use.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown that coxsackievirus also induces anti-tumour activity against myeloma through activating pDCs and NK cells. 23 In addition, lenalidomide has been Combined effects of T-01 and lenalidomide. (A) Cell lines were treated with the indicated concentrations of lenalidomide for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…CVA21 stimulated potent anti-tumor immune responses. These included cytokine-mediated bystander killing, enhanced NK cell-mediated cellular cytotoxicity and priming of tumor-specific CTLs [128]. CVA21 also induced immunogenic apoptosis in bladder cancer cell lines, as evidenced by ICD determinants calreticulin and release of HMGB1.…”
Section: Comparison Of Ndv To Other Ovsmentioning
confidence: 99%